A Monograph of the British Fossil Corals : Second Series - Duncan, P. Martin (Place of publication not identified : publisher not identified, 1866)
In this supplementary monograph, originally published 1866-72, the English geologist Peter Martin Duncan (1824-91) treats only those British fossil corals that were unknown to Edwards and Haime in their preceding monograph (also reissued in this series), and those that needed revision. The two works were meant to be used together, and Duncan includes combined indexes. Featuring similar white-on-black engravings, the work starts with the Eocene and proceeds stratigraphically downwards, ending with corals from around the Triassic-Jurassic boundary. The intention to cover Palaeozoic corals was never fulfilled, so this monograph concerns scleractinians. Duncan includes an introductory treatment of the anatomy of living scleractinians, in support of his claim to offer a new taxonomical approach. He also draws attention to'the entirely new [Eocene (Bartonian)] Coral-fauna of Brockenhurst'. This was auspicious, since recent study of this fauna sheds light on the origin of the modern Indo-Pacific coral hotspot.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).